Is There a Rationale for Author Byline Order? A Case Study of the Journal of Informetrics - Hilário, Carla Mara (2022)
Multiple authorship on research publications is common in many disciplines. Is the order in which authors appear in the byline determined by consistent criteria? This study investigated co-authored papers published in the Journal of Informetrics in 2016, the year in which this representative journal of the area of informetrics started to publish the articles with the author contributions form, as a case study to determine if there is consistency in the author order based on author contributions. For the papers studied, there was greater consistency for the first and last authors, and less consistent rationale for the order of the remaining author positions for the papers studied. A survey sent to the authors of the publications studied revealed that authors believed the first and last author positions played a more distinctive role. The lack of agreement and function of author order in other positions raises the question about the significance of author order and its purpose in determining the credit authors receive for co-authored publications.